WRITING AS A NARRATIVE HOME (PALIMPSEST / ПАЛИМПСЕСТ, 2018)
Starting from the premise about the exile as a paradigmatic phenomenon of 20th century, this paper is focused on narrative representations of the exile within the Balkan literary context. The theoretical background of this elaboration is double: on one side - the reflections on exile offered by Edward Said and Sophia A. McClennen; on the other side - the theses by Martin Wallace about the novel „as oppositional discourse“. In accordance to this, the concrete subject of interest is narrative representations of the exile, founded on personal exile experience. The interpretative focus based on texts written from the position of the subject in exile follows several levels:  thematization of exile as writing in/about exile; tensions between the experience of the exile and its representation/narrativization/ fictionalization; counterpoint aspects in representations of exile through the complex of dialectical tensions.